Evaluation of SLE Susceptibility Genes in Malaysians - Molineros, Julio E. (Hindawi Publishing Corporation, 2014)
Systemic Lupus Erythematosus (SLE) is a clinically heterogeneous autoimmune disease with strong genetic and environmental components. Our objective was to replicate 25 recently identified SLE susceptibility genes in two distinct populations (Chinese (CH) and Malays (MA)) from Malaysia. We genotyped 347 SLE cases and 356 controls (CH and MA) using the ImmunoChip array and performed an admixture corrected case-control association analysis. Associated genes were grouped into five immune-related pathways. While CH were largely homogenous, MA had three ancestry components (average 82.3% Asian, 14.5% European, and 3.2% African). Ancestry proportions were significantly different between cases and controls in MA. We identified 22 genes with at least one associated SNP (P < 0.05). The strongest signal was at HLA-DRA (P (Meta) = 9.96 × 10(−9); P (CH) = 6.57 × 10(−8), P (MA) = 6.73 × 10(−3)); the strongest non-HLA signal occurred at STAT4 (P (Meta) = 1.67 × 10(−7); P (CH) = 2.88 × 10(−6), P (MA) = 2.99 × 10(−3)). Most of these genes were associated with B- and T-cell function and signaling pathways. Our exploratory study using high-density fine-mapping suggests that most of the established SLE genes are also associated in the major ethnicities of Malaysia. However, these novel SNPs showed stronger association in these Asian populations than with the SNPs reported in previous studies.